SEEING DATA, FEELING NUMBERS: HOW PEOPLE INTERACT WITH DATA VISUALISATIONS - Kennedy, Helen; Hill, Rosemary Lucy (AoIR Selected Papers of Internet Research, 2015)
Whilst there has been considerable attention to the development of strategies to maximise effectiveness in data visualization research, only some of this has engaged actual users in the research process. Practitioners and researchers alike agree that historically, the field has lacked a user-centred knowledge base. Research which engages users often provides little information about who they are and how this might affect their engagement with visualizations. Research into user engagement with visualizations almost never considers the socio-cultural factors that affect how people engage and some research even attempts to bypass or ‘overcome’ such factors. Drawing on qualitative, empirical research with users of visualizations on Seeing Data: are good big data visualisations possible? (http://seeingdata.org), in this paper we identify six factors that affect engagement, which we define as socio-cultural: subject matter; source/media location; beliefs and opinions; time; emotions; and confidence and skills. We argue that to fully understand engagements with visualizations, it is important to acknowledge these factors. We conclude by reflecting on what these findings mean for how ‘effectiveness’ could and should be defined in relation to data visualizations. Our research suggests that the study of engagement with visualizations, to date primarily carried out within fields such as HCI or computing, can benefit from adopting qualitative approaches developed within media studies, specifically in relation to media audience research.